Aligning Future Employee Action and Corporate Strategy in a Resource-scarce Environment - Anders Kryger (Copenhagen Business School (CBS), 2018)
Can employees' planned future actions and company strategy be aligned in a resource-scarce organization, and if so how? So begins this action research Industrial PhD study that zooms in on the time period that preceded the implementation of a deliberate, top-down strategy at a resource-scarce diesel engine company, and followed its development. The research question takes a point of departure in a seemingly simple task: to align action planning with a strategy. This simplicity is deceptive, however, since in reality such alignment is a highly complex and challenging endeavor for organizations – and more so in an environment of resource scarcity brought on by a market downturn which forces managers to think in shortterm deliverables and to deprioritize long-term activities and setting a new strategic direction. Resource scarcity places time and financial constraints on strategy consultants' possibilities to support strategy implementation: managers and their employees have little – if any – time to familiarize themselves with the new strategy, let alone think about how their own actions can support the strategy. To maximize complications, add a layer of pronounced organizational problems that needs to be solved at the same time.
hdl:10398/9667
Keywords: 650